2021
DOI: 10.1371/journal.pone.0256749
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular imaging with QUTE-CE MRI in APOE4 rats reveals early vascular abnormalities

Abstract: Cerebrovascular abnormality is linked to Alzheimer’s disease and related dementias (ADRDs). ApoE-Ɛ4 (APOE4) is known to play a critical role in neurovascular dysfunction, however current medical imaging technologies are limited in quantification. This cross-sectional study tested the feasibility of a recently established imaging modality, quantitative ultra-short time-to-echo contrast-enhanced magnetic resonance imaging (QUTE-CE MRI), to identify small vessel abnormality early in development of human APOE4 kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…and in pericytes E4-lower genes were enriched in cell migration regulation, transport across BBB (ATP1A2, SLC6A13, SLC19A1, SLC6A1), and cell-cell junction maintenance (CSF1R, TJP1) ( Fig. 6b ), in agreement with reports of ApoE ε4 individuals showing reduced cerebral blood flow 112 , and cerebrovascular abnormalities 113 . APOE4-higher genes were significantly enriched for cytokine response in both capillary endothelial cells and pericytes, negative regulation of cell migration in capillary endothelial cells, and apoptotic process and positive regulation of endocytosis in pericytes ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…and in pericytes E4-lower genes were enriched in cell migration regulation, transport across BBB (ATP1A2, SLC6A13, SLC19A1, SLC6A1), and cell-cell junction maintenance (CSF1R, TJP1) ( Fig. 6b ), in agreement with reports of ApoE ε4 individuals showing reduced cerebral blood flow 112 , and cerebrovascular abnormalities 113 . APOE4-higher genes were significantly enriched for cytokine response in both capillary endothelial cells and pericytes, negative regulation of cell migration in capillary endothelial cells, and apoptotic process and positive regulation of endocytosis in pericytes ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…Other preclinical technologies for visualizing BBB disruption are also being actively investigated, but have not yet been tested in human patients. Some of these technologies include dual-wavelength high-resolution photoacoustic microscopy (Wang et al, 2022), PET-MRI nanoparticles (Debatisse et al, 2020), and quantitative ultra-short time-to-echo contrast-enhanced MRI (Leaston et al, 2021); however, more research is necessary to assess their diagnostic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al reported using diffusion-weighted imaging assisted with monocrystalline iron oxide nanoparticle for assessing the abnormalities in the vessel size index, diameter, density, mean vessel-weighted image, and blood volume fraction in 5 × FAD mice compared to wild-type mice [ 203 ]. Leaston et al showed early vascular abnormalities in APOE4 knock-in rats compared to wild-type rats by using quantitative ultra-short time-to-echo (QUTE) CE-MRI [ 202 ]. MR elastography has been used to detect the impaired cerebral viscoelastic properties in 5 × FAD, APP/PS1, and APP23 mice [ 206 , 207 , 208 ].…”
Section: Cerebrovascular Imagingmentioning
confidence: 99%